Antibacterial Activity of Pluchea indica and Piper betle Ethanol Extract on Staphylococcus epidermidis and Pseudomonas aeruginosa - Nela Simanjuntak; Umi Yuniarni; Diki Prayugo (Universitas Padjadjaran, Indonesia)
Medicinal plants are widely used for the treatment of different infectious diseases. This study was aimed to investigate antibacterial activity of Pluchea indica (P. indica) and Piper betle (P.betle) ethanol extract on Staphylococcus epidermidis (S. epidermidis) and Pseudomonasaeruginosa (P. aeruginosa) using agar disk diffusion method. Ethanol extract of Piper betle showed more potent antibacterial activity than P. indica against S. Epidermidis with the highest inhibiton zone at 30.71 mm and 21.73 mm from 1 mg/ml concentration, respectively. In contrast, against P. aeruginosa, the ethanol extract of P. indica was more potent than P. betle with 21.44 mm and 20.12 mm of inhibition zone on 1 mg/ml concentration, respectively. There was no increased effect from the combination of these two extracts against these bacteria. When comparing the antibacterial activity of these extract with tetracycline asthe standard, we found that antibacterial activity of P. indica at the concentration of 0.9 mg/ ml was comparable with that of tetracycline at concentration of 12.52 μg/ml, while P. betle needed 0.3 mg/ml concentration to had similar activity with 10.51 μg/ml of tetracycline. In conlusion, the antibacterial activity of ethanol extracts of P. indica and P. betle indicated that these extract had sufficient potential to warrant further examination and development as a new antibacterial agent.Keywords: Pluchea indica, Piper betle, antibacterial, agar disk diffusion